Increased prevalence of gastrointestinal symptoms and disorders of gut‐brain interaction during the COVID‐19 pandemic: An internet‐based survey. Issue 2 (18th June 2021) - Nakov, Radislav; Dimitrova‐Yurukova, Desislava; Snegarova, Violeta; Nakov, Ventsislav; Fox, Mark; Heinrich, Henriette
Abstract: Background: Quarantine with social distancing has reduced transmission of COVID‐19; however, fear of the disease and these remedial measures cause anxiety and stress. It is not known whether these events have impacted the prevalence of gastrointestinal (GI) symptoms and disorders of brain‐gut interaction (DGBI). Methods: An online platform evaluated the prevalence of GI symptoms during the COVID‐19 pandemic. Data collection utilized validated questionnaires and was fully anonymized. Findings were compared with identical data acquired in 2019. The association of results with stress and anxiety was analyzed. Results: Data were collected from 1896 subjects May ‐ August 2019 to 980 non‐identical subjects May ‐ June 2020. GI symptoms were reported by 68.9% during the COVID‐19 lockdown compared with 56.0% the previous year ( p  < 0.001). The prevalence of irritable bowel syndrome (26.3% vs. 20.0%; p  < 0.001), functional dyspepsia (18.3% vs. 12.7%; p  < 0.001), heartburn (31.7% vs. 26.2%, p  = 0.002), and self‐reported milk intolerance (43.5% vs. 37.8% p  = 0.004) was higher during the pandemic. Many individuals reported multiple symptoms. Anxiety was associated with presence of all GI symptoms. High levels of stress impacted functional dyspepsia ( p  = 0.045) and abdominal pain ( p  = 0.013). The presence of DGBI ( p  < 0.001; OR 22.99), self‐reported milk intolerance ( p  < 0.001; OR 2.50), and anxiety ( p  < 0.001; OR 2.18) was independently associated with increased GI symptoms during COVID‐19 pandemic. Conclusions: The prevalence of GI symptoms was significantly higher during the COVID‐19 lockdown than under normal circumstances the previous year. This increase was attributable to increased numbers of patients with DGBI, an effect that was associated with anxiety. Abstract : The prevalence of GI symptoms is significantly higher during the COVID‐19 lockdown in 2020 than under normal circumstances in 2019. This increase is attributable to increased numbers of patients with DGBI, an effect that is associated with anxiety.